Modelling the bearing and branching behaviors of 1-year-old shoots in apricot genotypes - Mészáros, Martin; Guédon, Yann; Krška, Boris; Costes, Evelyne (PLoS One, 2020)
In most temperate fruit trees, fruits are located on one-year old shoots. In Prunus species, flowers and fruits are born in axillary position along those shoots. The axillary bud fate and branching patterns are thus key components of the cultivar potential fruit production. The objective of this study was to analyze the branching and bearing behaviors of 1-year-old shoots of apricot cultivars and clones genetically closely related. Shoot structures were analyzed in terms of axillary bud fates using hidden semi-Markov chains and compared depending on the genotype, year and shoot length. The shoots were composed of three successive zones containing latent buds (basal zone), central flower buds (median zone) and vegetative buds (distal zone), respectively. The last two zones contained few associated flower buds. The zones length (in number of metamers) and occurrence strongly depended on shoot development in the two successive years. With decrease in the number of metamers per shoot, the last two zones become shorter or may not develop. While the number of metamers of the basal and distal zones and the number of associated flower buds correlated to the number of metamers of the shoot, the number of metamers of the median zone and the transition probability from the median to the distal zone were cultivar specific.
Keywords: neparametrická statistika; Plant Shoots; Markovovy řetězce; genotyp; meruňka obecná; květy; Markov Chains; Prunus armeniaca; výhonky rostlin; ovoce; Statistics, Nonparametric; Models, Biological; Fruit; Flowers; biologické modely; Genotype